Keberlanjutan Usaha Kemplang Mikro - Dasir Dasir; Erliza Yuniarti; Diah Isnaini Asiati (MBIA, 2019)
The business of managing Kerupuk Kemplang as one of Palembang’sspecial foods is mostly managed by household. One of businesss is “Ibu Mai”. Although tihis business has been going on for a long time, its sustainability has several obstacles. The study was conducted to find out some aspects that cause its sustainability. The study uses primary data collected through observation and interviews. The analysis technique is done qualitatively with the induction analysis approach. The results were obtained 1) Production aspects, there were constraints on the avaibility of unstable fish and equipment that does not support 2) Financial aspects, adequate financial administration has not been used so it is difficult to know the flow of expenditure and income as a basis for determining profits 3) Market aspects, not all the market can be served so that the potential for development is still large 4) the aspect of human resources, because the production process is simple the labor force is considered to be sufficient.